Analisis Dampak Manajemen Strategis terhadap Kinerja UMKM di Provinsi Lampung - Suryani Suryani (Business Perspective Journal, 2023)
This study aims to analyze the impact of strategic management on the performance of Micro, Small and Medium Enterprises (MSMEs) in Lampung Province. MSMEs have a significant role in regional and national economic growth, but the challenges faced by MSMEs often affect their overall performance. This study uses a qualitative approach by collecting data/information through interviews with several MSME actors/owners operating in Lampung Province. The in-depth and structured interviews focused on strategic management aspects, including strategic planning, strategy implementation, control and performance evaluation. In addition, MSME performance data is also collected, such as sales growth, profitability, operational efficiency, and market share. The results of this study indicate that MSMEs that implement strategic management well tend to achieve better performance than those who focus less on this aspect. Good strategic planning allows MSMEs to have a clear long-term vision and goals, while effective strategy implementation helps them to better face market challenges. Tight control allows SMEs to respond quickly to changing situations, and regular performance evaluations allow them to improve weaknesses and capitalize on existing potential. Keywords: performance, strategic management, SMMEs.